International Advertising and Communication Current Insights and Empirical Findings - Diehl, Sandra.; Diehl, Sandra.; Terlutter, Ralf.; Terlutter, Ralf. (Forschungsgruppe Konsum und Verhalten,, 2006)
This volume presents a wide selection of studies and works in the area of international communication. The growing globalisation of markets requires of firms to take an increasingly international orientation in developing communication policies. The goal of this book is to contribute to more systematic research in this field. Renowned communication researchers from Europe, the U.S., Asia and Australia have contributed to the making of this book. This mix of international authors offers the reader a comprehensive overview of current thinking and cutting-edge research in the area of international advertising and communication. The book includes seven main areas: " Advertising and Communication Effects " Advertising and Information Processing " Communication and Branding " Emotional, Social and Individual Aspects of Communication " Communication and New Media " International Advertising " Perspectives on the Future of International Advertising.